Computational Thinking and Coding for Young Children: A Hybrid Approach to Link Unplugged and Plugged Activities - Daisuke Akiba (MDPI AG, 2022)
In our increasingly technology-dependent society, the importance of promoting digital literacy (e.g., computational thinking, coding, and programming) has become a critical focus in the field of childhood education. While young children these days are routinely and extensively exposed to digital devices and tools, the efficacy of the methods for fostering digital skills in the early childhood classroom has not always been closely considered. This is particularly true in settings where early childhood educators are not digital experts. Currently, most of the efforts in standard early childhood settings, taught by teachers who are not digital experts, appear to revolve around "unplugged" activities that do not directly involve digital tools or devices, and it is not entirely clear how well these "unplugged" lessons promote the corresponding skills in "plugged" settings, such as coding and programming. This article discusses how, through further research, we may be able to devise an effective method for seamlessly building digital literacy among young children, transcending the "unplugged vs. plugged" barriers effortlessly.